The Development of Metacognition: How it Defines and How it can be Done - Wen Ma; Xiufang Wang; Bo Zhang (An Overview of Literature, Language and Education Research Vol. 9, 2025)
The development of metacognition is illustrated by five studies. They are defined as self-management skills, metacognitive knowledge and metamemory. The development of metacognition begins at preschool-aged children in a variety of classroom activities. There is now consensus amongst researchers that metacognition consists of both metacognitive knowledge and the processes of regulation and control of cognition. These researchers provide evidence of young children’s awareness of and capability to understand mental activity to regulate cognition and emotions.